We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
90
3
avatar

If abc=13 and\(\left(a+\frac{1}{b}\right)\left(b+\frac{1}{c}\right)\left(c+\frac{1}{a}\right)=\left(1+\frac{1}{a}\right)\left(1+\frac{1}{b}\right)\left(1+\frac{1}{c}\right),\)find a+b+c.

 

Thank you in advance :)

 Oct 6, 2019
 #1
avatar+8810 
+2

Let's start by expanding both sides and combining like terms:

 

\(\begin{array}{rcl} \left(a+\frac{1}{b}\right)\left(b+\frac{1}{c}\right)\left(c+\frac{1}{a}\right)&=& \left(1+\frac{1}{a}\right)\left(1+\frac{1}{b}\right)\left(1+\frac{1}{c}\right)\\~\\ \left(ab+\frac{a}{c}+1+\frac{1}{bc}\right)\left( c+\frac{1}{a} \right)&=&\left(1+\frac{1}{b}+\frac{1}{a}+\frac{1}{ab} \right)\left( 1+\frac{1}{c}\right)\\~\\ abc+b+a+\frac{1}{c}+c+\frac{1}{a}+\frac{1}{b}+\frac{1}{abc}&=& 1+\frac{1}{c}+\frac{1}{b}+\frac{1}{bc}+\frac{1}{a}+\frac{1}{ac}+\frac{1}{ab}+\frac{1}{abc}\\~\\ abc+b+a+{\color{gray}\frac{1}{c}}+c+{\color{gray}\frac{1}{a}}+{\color{gray}\frac{1}{b}}+{\color{gray}\frac{1}{abc}}&=& 1+{\color{gray}\frac{1}{c}}+{\color{gray}\frac{1}{b}}+\frac{1}{bc}+{\color{gray}\frac{1}{a}}+\frac{1}{ac}+\frac{1}{ab}+{\color{gray}\frac{1}{abc}}\\~\\ abc+b+a+c&=&1+\frac{1}{bc}+\frac{1}{ac}+\frac{1}{ab}\\~\\ abc+a+b+c&=&1+\frac{a}{abc}+\frac{b}{abc}+\frac{c}{abc}\\~\\ abc+a+b+c&=&1+\frac{a+b+c}{abc} \end{array}\)

 

 

At this point, let's substitute   x   in for   a + b + c   and   13   in for   abc    so we want to solve this for  x:

 

\(\begin{array}{ccc} 13+x&=&1+\frac{x}{13}\\~\\ 169+13x&=&13+x\\~\\ 13x-x&=&13-169\\~\\ 12x&=&-156\\~\\ x&=&-13 \end{array}\)_

 Oct 6, 2019
 #2
avatar+2417 
+2

Dang thats a lot of work! But a good problem solved.

CalculatorUser  Oct 6, 2019
 #3
avatar
+1

THANK YOU SO MUCH :)

 Oct 7, 2019

6 Online Users